Influence Of Electronic Service Quality And Brand Trust On Customer Loyalty Through BRImo Product Image - Budiani, Anna; Sopiah, Sopiah; Siswanto, Ely (Journal of Applied Business, Taxation and Economics Research, 2025)
Today's digital banking world is no longer an option, but has become the main requirement in banking transactions in the digitalization era. Customer needs have shifted to demands for easy, fast, and reliable services. Related to this, banks must have digital services such as customer service that is always on-time and a reliable back office in fulfilling various customer needs related to digital banking transactions. The use of ATM machine facilities, Internet Banking, SMS Banking and Mobile Banking as a form of the trend of the phenomenon of digitization of banking services can support the quality of service (service quality) of national banking. Through the presence of digital machines, users can enjoy banking services anywhere (banking everywhere) with the speed and convenience offered by digital products. BRI mobile as a mobile banking service that has been widely used by the public needs to maintain customer loyalty to get the maximum benefit from transactions made by its customers. This study aims to determine the effect of electronic service quality (KLE) and brand trust (KM) on customer loyalty (LN) through product image (CP) on BRImo users at PT.bank Rakyat Indonesia.Tbk Branch Office Probolinggo by answering 7 (seven) hypotheses. This study uses a quantitative approach using the partial least squares equation model (PLS-SEM). The sample in this study were BRI Savings customer respondents who used the BRImo application for less than 3 (three) years to more than 5 (five) years using non-probability sampling techniques. The results of the analysis show that KM has a positive and significant effect on LN, as well as CP has a positive and significant effect on LN. Meanwhile, KLE has no significant effect on LN. Furthermore, the results show that CP is able to mediate the relationship between KM and LN, although it cannot mediate the relationship between KLE and LN. The implications of these findings can provide a theoretical basis and reference for BRI to focus their attention on the importance of effectively utilizing brand trust in developing product image to influence customer loyalty.